ETIOPATHOGENESIS AND CLINICAL PICTURE OF ACUTE LUNG ABSCESSES - Okhunov, A.O. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Treatment of purulent diseases of the lungs and pleura invariably remains an urgent problem. This pathology, painful for the patient, time-consuming for the doctor and expensive for the medical institution, combines intoxication due to a purulent-destructive process and impaired respiratory function. The occurrence of infectious destruction of the lungs and pleura is facilitated by immunodeficiency and immunosuppression, which are characteristic of patients suffering from haematological diseases, increased tendency to thrombosis, diabetes mellitus, alcoholism, drug addiction, HIV infection, who have undergone extensive surgical interventions, organ and tissue transplantation. Despite the widest use of antibacterial drugs, it is not possible to avoid purulent-destructive and gangrenous complications of pneumonia. This review scientific article is devoted to the problems of acute lung abscesses, namely the aetiology, pathogenesis and clinical picture of this disease.